1971
DOI: 10.1111/j.1471-0307.1971.tb01871.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Seasonal Variation and Conditions of Milk Production on the Bacteriological Quality of Refrigerated Farm Vat Milk Supplies

Abstract: SUMMARY The bacterial content of daily collected refrigerated farm vat milk from 94 farms in a traditionally dairying district in South Wales was appreciably higher during summer than in winter. This applied to total colony count, thermoduric count and coli‐aerogenes organisms content all determined at 30°C, and even to resazurin reduction in 2 h at 37°C. The type of milking plant and different methods of in‐place cleaning had quite a marked effect on the bacterial content of the milk. Milk from farms with cow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1971
1971
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Soler et al (1995) reported higher total bacterial, psychrotrophic, thermoduric, and coliform counts in summer and lower counts in winter. Similar results were observed earlier by Jones et al (1971), who indicated that higher summer temperatures might allow the growth of thermoduric and coliform bacteria on milking equipment especially under improper cleaning and sanitation of milking equipment. Our counts were in agreement with the previous results with regard to occurrence of lower counts in winter; however, high counts did not follow a consistent pattern for PIC and LPC.…”
Section: Seasonal Variationssupporting
confidence: 90%
“…Soler et al (1995) reported higher total bacterial, psychrotrophic, thermoduric, and coliform counts in summer and lower counts in winter. Similar results were observed earlier by Jones et al (1971), who indicated that higher summer temperatures might allow the growth of thermoduric and coliform bacteria on milking equipment especially under improper cleaning and sanitation of milking equipment. Our counts were in agreement with the previous results with regard to occurrence of lower counts in winter; however, high counts did not follow a consistent pattern for PIC and LPC.…”
Section: Seasonal Variationssupporting
confidence: 90%
“…Further evidence of the practical merit of the ABW system of cleaning pipeline milking plants was reported by Jones, Williams & Thomas (1971) during an investigation of the bacteriological quality of farm bulk tank milk produced on 93 fitrms. The total, thermoduric and coli-aerogenes organisms content of the milk supplies from the 17 farms where the milking plants uere cleansed by the ABW system were appreciably lower than those for milk from the 76 farms where circulation cleaning was being employed.…”
Section: Pipeline Milking Plantsmentioning
confidence: 93%